The Effect of Subscription Strategies, Personalized Offers, and Email Marketing on Perceived Usefulness through User Engagement and Its Impact on Conversion and Customer Retention in Local Indonesian Streaming Services - Sudirjo, Frans; Priyana, Yana; Lesmana, Tera (West Science Interdisciplinary Studies, 2025)
This study examines the influence of subscription strategies, personalized offers, and email marketing on perceived usefulness through user engagement, and their impact on conversion and customer retention in Indonesian local streaming services. Using a quantitative approach, data were collected from 300 respondents through a structured questionnaire using a 5-point Likert scale and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that all three marketing strategies significantly enhance user engagement, with personalized offers having the strongest effect. User engagement strongly predicts perceived usefulness, which in turn significantly drives both conversion and customer retention. These findings confirm the mediating role of user engagement and perceived usefulness in the relationship between marketing strategies and business performance outcomes. The study contributes to the theoretical understanding of user behavior in digital entertainment services and provides practical recommendations for optimizing customer acquisition and loyalty in competitive streaming markets.